EFEKTIVITAS PENGGUNAAN MEDIA “KPS” UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK FASE B SEKOLAH DASAR - Fathimah Az-Zahra; Ani Hendriani; Rosiana Mufliva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the problem of low ability to understand mathematical concepts in the material of multiplication counting operations in phase B elementary school students. This is due to the limited use of learning media during the learning process, so it is necessary to use concrete learning media, namely “KPS” media. This study aims to analyze the effectiveness of the use of “KPS” media on improving the ability to understand the mathematical concepts of phase B students on multiplication material. The research method uses a quantitative approach with a pre-experimental design, namely one group pre-test-post-test. The research sample was third grade students totaling 19 people. The results showed that there was a significant increase in the mathematical procedural fluency of students between before and after treatment. This is evidenced by the mean difference test using the Paired Sample T-test. In addition, based on the results of the difference test on the N-Gain score, the effectiveness of using the “KPS” media is in the high criteria. Therefore, it can be concluded that the use of “KPS” media is effective enough to improve the understanding of mathematical concepts of phase B students precisely in class III on the material of multiplication counting operations.